(untitled) (UUM Journal of Legal Studies, 2025)
In the realm of law, technology is utilized to cope with the influx of smart contracts to replace traditional contracts that govern contractual dynamics. Smart contracts differ from traditional contracts as they rely on computer codes to fulfill the contractual obligations of the involved entities. This article discusses the current state of Iraqi contract law and assesses the feasibility of integrating Iraqi law to manage and implement smart contracts within the Iraqi legal system. The study employs a qualitative approach and adopts comparative doctrinal research to investigate current legal practices, the relevant legislation, and the adaptation of Iraqi laws to smart contracts. As a result, the study reveals the inadequacy of Iraqi contract law in incorporating smart contracts into existing legal practices in Iraq. It also underscores the necessity of enacting new laws to explicitly regulate the operation of smart contracts involving the use of cryptocurrencies.